A maximum power point tracking strategy applied to building integrated photovoltaics. Issue 1 (21st December 2021) - Cui, Jian; Fang, Jianjun
Abstract: To solve the problem of permanent-shadow shading of photovoltaic buildings, a maximum power point tracking (MPPT) strategy to determine the search range by pre-delimiting area is proposed to improve MPPT efficiency. The single correspondence between the solar-cell current–voltage ( I – V) curve and the illumination conditions was proved by using the single-diode model of photovoltaic cells, thus proving that a change in the illumination conditions corresponds to a unique maximum power point (MPP) search area. According to the approximate relationship between MPP voltage, current and open-circuit voltage and short-circuit current of a photovoltaic module, the voltage region where the MPP is located is determined and the global maximum power point is determined using the power operating triangle strategy in this region. Simulation carried out in MATLAB proves the correctness and feasibility of the theoretical research. Simulation results show that the MPPT strategy proposed in this paper can improve the average efficiency by 1.125% when applied in series as building integrated photovoltaics. Abstract : To solve the problem of permanent-shadow shading of building integrated photovoltaics (BIPV), a maximum power point tracking strategy is proposed and simulated. The strategy proposed in this paper improved the average efficiency by 1.125% when tested on PV strings in series in a BIPV application. Graphical Abstract: